Efficacy of phage therapy in controlling staphylococcal biofilms: a systematic review - Zahra Mobarezi; Amir Hossein Esfandiari; Samaneh Abolbashari; Zahra Meshkat (European Journal of Medical Research)
Abstract Background Antibiotic-resistant bacteria pose an urgent health threat as mutations have led to resistant strains that evade treatment. These bacteria form biofilms, complicating infection management. Bacteriophages are being recognized for their potential in phage therapy due to their effectiveness in rapidly targeting and eliminating bacterial hosts. Materials and methods This systematic review examined the effectiveness of bacteriophages against biofilms created by antibiotic- and drug-resistant staphylococcal strains. A thorough search of the Embase, Web of Science, PubMed, and Scopus databases was conducted for studies published from 2012 to October 29, 2024, focusing on relevant research while excluding irrelevant studies. Results This systematic review assesses the effectiveness of phage-derived enzymes, including endolysins and depolymerases, as well as whole bacteriophages, in degrading biofilms and clearing bacteria. It also highlights how combining phages with antibiotics or other agents can improve biofilm removal. The review explores the potential applications of phage therapy in various contexts, such as infections related to milk, silicone surfaces, synovial fluid, and prosthetic joint materials. Overall, while phage therapy shows promise as an alternative to antibiotics, additional research is necessary to refine treatment methods and ensure safety. Conclusions Bacteriophages hold potential as a standalone treatment and a complementary option to traditional antibiotics for managing S. aureus biofilms, but further research is needed to understand their clinical potential. Additional studies on phage selection, dosing, and administration methods are necessary, along with exploration of phage–antibiotic synergy mechanisms and assessment of the safety and environmental impacts of phage therapy.